Ankle and Foot Ultrasound: Reliability of Side‐to‐Side Comparison of Small Anatomic Structures. (28th December 2018) - Rossi, Federica; Zaottini, Federico; Picasso, Riccardo; Martinoli, Carlo; Tagliafico, Alberto Stefano
Abstract : Objectives: In sonography of clinically relevant small structures of the ankle and foot, the healthy contralateral side can be used as a reference to identify subtle abnormalities. Intrasubject side‐to‐side variability must be minimal. The aim of this study was to assess the reliability of side‐to‐side sonographic evaluation of small structures of the ankle and foot. Methods: Thirty healthy volunteers were prospectively studied. Small structures of the ankle and foot were evaluated bilaterally by 2 musculoskeletal radiologists in separate sessions. The deep peroneal nerve, superior extensor retinacula, calcaneofibular ligament, superior peroneal retinacula, tibialis posterior tendon, tibial nerve, Achilles tendon, plantaris tendon, plantar fascia, and sural nerve were considered. To assess intra‐ and interreader agreements, 30 (100%) examinations were repeated. A nonparametric statistic was used. Results: Data were not normally distributed ( P > .001). Intrareader agreement was k = 0.67 (95% confidence interval, 0.57–0.78) and interreader agreement was k = 0.73 (95% confidence interval, 0.68–0.77). The mean values and standard deviation for all the structures were 0.36 ± 1.85 mm. The overall coefficient of variation was 18.5%. The intraclass correlation coefficient was 0.93 (95% confidence interval, 0.92–0.94). Conclusions: In ankle and foot sonography, the healthy contralateral side can be used as a reference during a real‐time musculoskeletal ultrasound evaluation of small structures.